Implementasi Point of Sales menggunakan Metode EOQ Berbasis WEB - Ahmad Fajar; Dr. Fauziah; Nur Hayati (Jurnal KomtekInfo, 2021)
Point of sales (POS) is a system used to process sales transactions, stock goods and process data. This system is built based on web and PHP and MYSQL programming language with stock management method, namely Economic Order Quantity (EOQ). The EOQ method is a method used to determine the order of goods or purchases of goods that must be made and how many items to order. In the conventional method of determining an order in the amount of 1,200 units in one year, the ordering cost is Rp. 210,000, the price per unit is Rp. 897,955 and 5% storage. Business actors use the conventional method by purchasing 200 units with a total of 6 times and a safety stock of 50. In this study the authors use the EOQ method calculation to determine the number of goods 1200 per year. Then it will produce 106 orders of goods with a frequency of 11 times safety stock 15 and ROP 24. The conclusion of this study is to make stock calculations using the EOQ method in purchasing goods more efficiently than manual / conventional methods.